ARCHITECTURE OF UNIVERSITY EDUCATIONAL PROCESSES IN THE CONDITIONS OF THE COVID-19 PANDEMIC: - Inna Vladimirovna Ershova; Ekaterina Evgenievna Enkova; Vasily Andreevich Laptev; Andrey Yurievich Petrakov (International Journal of Law in Changing World)
The paper focuses on the degree of influence of Big Data on building the educational process at the Russian Law University during the COVID-19 pandemic. We use the sociological method as the primary research method. The result shows the influence of the collected information on administrative decision-making. Additionally, we describe the educational process within the selected university. The paper demonstrates student attitude toward Big Data in various aspects, including awareness of the technology and its significance for the university's management. We conclude that Big Data has not yet been widely used in Russian higher education. Therefore, we identify the reasons preventing the use of Big Data in education. This research novelty lies in pointing to Big Data's impact on the architecture of the university educational process in different periods of the COVID-19 pandemic when higher education institutions implemented distance or mixed learning and online communications.